1993
DOI: 10.3109/03005369309076699
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of evoked otoacoustic emissions as an in-patient hearing check after meningitis

Abstract: The desirability of finding children with hearing impairment after bacterial meningitis as soon as possible prompted us to examine the feasibility of using evoked otoacoustic emissions (EOAE) as an in-patient check of hearing status in children recovering from bacterial meningitis. Sixty-six episodes of bacterial meningitis were studied. Traces could be recorded for only 54.7% of ears. All children subsequently found to have sensorineural hearing impairment who were tested with EOAE, failed the screening test.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Populations that could be screened include children, such as those with severe learning difficulties, who are difficult to assess by conventional means.7 Another potential group consists of those children who have a particularly high risk of hearing impairment after meningitis8 9 or the use of ototoxic drugs.3 8 It has also been proposed that TEOAEs could be used for universal preschool screening.10 To date, however, only two short reports have been published on the clinical use of TEOAE screening in children.9 10 Two major difficulties have been identified in the use of TEOAEs in older children. The first is that some children will not tolerate the test procedure.7 9 The second is that, despite the excellent sensitivity of the test, there may be an unacceptably high number of false positive results. "' This problem of low specificity is mainly due to the fact that the sound of the TEOAE signal is often obscured by other noise.'…”
mentioning
confidence: 99%
“…Populations that could be screened include children, such as those with severe learning difficulties, who are difficult to assess by conventional means.7 Another potential group consists of those children who have a particularly high risk of hearing impairment after meningitis8 9 or the use of ototoxic drugs.3 8 It has also been proposed that TEOAEs could be used for universal preschool screening.10 To date, however, only two short reports have been published on the clinical use of TEOAE screening in children.9 10 Two major difficulties have been identified in the use of TEOAEs in older children. The first is that some children will not tolerate the test procedure.7 9 The second is that, despite the excellent sensitivity of the test, there may be an unacceptably high number of false positive results. "' This problem of low specificity is mainly due to the fact that the sound of the TEOAE signal is often obscured by other noise.'…”
mentioning
confidence: 99%
“…The permanent hearing damage from meningitis occurs primarily at the cochlea and early in the illness. 27,31 Fortnum et al 32 concluded that OAE were not a practical method for a predischarge hearing check for post‐meningitic children as useful information could only be obtained in 53% of children tested. All failures occurred in children under 4 years of age because of poor cooperation with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify children with meningitis who become deaf it is recommended that all children at risk have a reliable assessment of their hearing by whatever means may be appropriate to their ages 3. Referral for a hearing assessment should be an essential part of the treatment protocol for all such children and should be performed 2–4 weeks after discharge to allow any middle ear deafness to resolve.…”
Section: Discussionmentioning
confidence: 99%